Elaboration of methodology for designing a publishing and printing web portal - Naumenko, Mariya; Hrabovskyi, Yevhen (Eastern-European Journal of Enterprise Technologies, 2018)
An analysis of features of designing publishing and printing web portals was performed. Based on these features, the key stages of the methodology of designing publishing and printing web portals have been established. It was found that because of the heterogeneous content of the publishing and printing portal as a complex internet project, it is advisable to adhere to the stage-by-stage and complexity conditions. Because of this circumstance, a necessity of working out a scenario of user interaction with the web portal arises. Solution of this issue is offered in this study. A matrix of logical interrelation was constructed, which makes it possible to study the cause-and-effect relationships of the basic functions performed by the publishing and printing portal. Based on the cause-and-effect relationships, structuring of the resource sections was made. By combining the tools of cluster, multivariate and discriminant analyses, the main sections of the publishing and printing web portal were defined and the content was formed. As a result, the structure of sections of the publishing and printing web portal was formed including reference, communicative, supplementary and information sections. The mechanism of ensuring safety of the publishing and printing web portals which provides reliable protection of the portal against information threats was proposed. To determine this mechanism, factors influencing enhancement of the publishing and printing portal safety, the matrix of pairwise comparison of safety factors and the matrix of weight coefficients of the safety factors were established.